Pengaruh Homophily Based Collaborative Learning dan Academic Engagement terhadap Writing Skill - Utomo, Prasetio; Degeng, Made Duanda Kartika; Soepriyanto, Yerry (Universitas Negeri Malang, 2024)
Writing skill is often regarded as a complex ability in English language learning, requiring more precision in grammar and vocabulary than listening, speaking, and reading. Teaching writing skills effectively requires special attention, such as implementing homophily-based collaborative learning, which groups students based on shared interests. This study also investigates the impact of academic engagement on writing skills. This quasi-experimental research employed a posttest-only control group design. The experimental class utilized homophily-based collaborative learning, while the control class used standard collaborative learning. Data were collected through questionnaires and posttests. The results indicated that the homophily-based collaborative learning class achieved higher writing skill scores compared to the standard collaborative learning class. Additionally, students with high academic engagement scored higher in writing skills than those with low academic engagement. No interaction was found between the learning model and academic engagement on writing skills. Therefore, teachers are encouraged to form learning groups based on homophily principles to achieve better outcomes and to provide additional support to learners with low academic engagement to optimize their results. Abstrak Writing skill seringkali dianggap sebagai keterampilan yang kompleks dalam pembelajaran Bahasa Inggris. Writing skill membutuhkan ketelitian dan kehati-hatian dalam grammar dan vocabulary yang lebih besar daripada listening, speaking, dan reading. Sebagai keterampilan yang kompleks, pembelajaran writing skill membutuhkan perhatian khusus agar pembelajaran dapat berjalan dengan optimal. Sebagai contoh dengan menerapkan collaborative learning dengan pembentukan kelompok berdasarkan prinsip homophily. Model ini menekankan mekanisme belajar secara kolaboratif berdasarkan peminatan topik belajar. Selain itu, penelitian terkait academic engagement juga perlu dilakukan untuk mengetahui pengaruhnya terhadap writing skill. Penelitian ini berjenis quasi experiment dengan posttest only control group design. Kelas eksperimen menggunakan homophily based collaborative learning sedangkan kelas kontrol dengan collaborative learning. Pengambilan data dilakukan dengan angket dan posttest. Penelitian ini menemukan kelas dengan homophily based collaborative learning memperoleh nilai writing skill yang lebih tinggi dibadingkan collaborative learning. Pebelajar dengan tingkat academic engagement yang tinggi juga menghasilkan nilai writing skill yang lebih tinggi dibandingkan academic engagement rendah. Tidak ditemukan adanya interaksi antara model pembelajaran, academic engagement, dan writing skill. Selanjutnya, guru dapat menyusun kelompok belajar berdasarkan prinsip homophily untuk mendapatkan hasil belajar yang lebih baik. Guru juga perlu memberikan perlakuan khusus kepada pebelajar dengan academic engagement rendah agar dapat mencapai hasil belajar yang optimal.